Spontaneous pneumomediastinum (Hamman's syndrome) following a vaginal delivery - Harjit S Dhaliwal (Barpeta Obstetrics and Gynaecological Society, 2019)
A 22 year old primigravida was reviewed on day 1 following a normal vaginal delivery. The patient reported neck swelling and pain. The pain was exacerbated by movement. She was not suffering from any chest pain nor had difficulties with breathing or swallowing. Diagnosis of spontaneous pneumomediastinum was made. Vaginal delivery complicated by pneumomediastinum and subcutaneous emphysema is rare, with a reported incidence as low as 1 in 100,000 deliveries. Treatment of Hamman's syndrome is supportive and the course is self- limiting.